Dermatitis herpetiformis - Dmochowski, Marian (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
In this comprehensive review, dermatitis herpetiformis is discussed according to the current understanding of this disease. Older concepts were also cited. The data of diagnostic and treatment procedures were considered from the pathogenetic point of view. Color instead of black-and-white microphotographs, including immunofluorescent ones, were enclosed to make readers realize how the real picture the pathologist is dealing with to make the correct diagnosis looks like.